Implications of cultural commodification of sinden on authenticity of local culture: a case study in Jimbe Village, Blitar District, East Java, Indonesia - Meifilina, Andiwi; Wisadirana, Darsono; Fatma Chawa, Anif; Kholifah, Siti (Technium Social Sciences Journal, 2020)
This article is a critical review of the impact of tourism that causes the commodification of local culture. Through a study in the Sinden Village in Jimbe Village, as the pioneer of the development of the Sinden art in Blitar District that has been established as pioneering village by the Tourism, Culture, Youth and Sport Services (DISPARBUDPORA) of Blitar Regency, this article attempts to discuss the cultural commodification of Sinden art as one of the Intangible Cultural Heritage. This article uses a qualitative method with a case study approach. Therefore, the data in this article was obtained by the researcher by using the interview techniques and direct observation. The findings show that the commodification of the Sinden culture does not completely change the authenticity of the Sinden culture. It is because the people of Jimbe village only commodify the supporting facilities of the Sinden culture, such as songs, the use of musical instruments, and wardrobes. Whereas, the authenticity of the Sinden culture itself is not determined by those, but rather from the delivery of messages and special singing techniques.